2017
DOI: 10.4236/cm.2017.84009
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Cranberry Extracts against Oxidative Stress and DNA Damage Induced by Diclofenac Sodium in Kidney of Male Albino Rate

Abstract: This work aimed to find the effect of cranberry extract (75 and 150 mg/kg•b•w) and vit. C (1 g/kg•b•w orally) on renal toxicity induced by Diclofenac sodium in male albino rats. Treated rats with diclofenac sodium with a concentration 150 mg/kg•b•w, expressed a significant increase in several parameters includes, plasma total cholesterol, LDL-cholesterol, and triglyceride as well as renal nitric oxide (NO), tumor necrosis factor-alfa (TNF-α) and TBARS. In addition, a significant reduction in renal superoxide d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…According to the results of the comet assay, it is evident that DIC caused DNA damage. This result was consistent with previous reports, 34,54 which reported DIC-induced genotoxicity and DNA fragmentation. Such DNA damage could be attributed to the oxidative stress caused by the release of ROS from DIC.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…According to the results of the comet assay, it is evident that DIC caused DNA damage. This result was consistent with previous reports, 34,54 which reported DIC-induced genotoxicity and DNA fragmentation. Such DNA damage could be attributed to the oxidative stress caused by the release of ROS from DIC.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, the current study was associated with lipid profile abnormalities, as evidenced by a significant rise in the levels of TC, TGs, and LDL-C and a decrease in the HDL-C level, consistent with prior reports. 54 These abnormalities might be the consequence of 'the significant inhibitory action of DIC on prostaglandin production. 55,56 It was found that diclofenac treatment significantly increased the serum MDA level while decreasing serum CAT and GPx activities.…”
Section: Biomaterials Science Papermentioning
confidence: 99%
“…Cupric ions react with protein in an alkaline solution to form a purple complex. The absorbance of this complex is proportional to the protein concentration in the sample [ 51 ]. Total Bilirubin (TB) and Lipid Peroxidation have been determined by following the method developed by Pearlman et al [ 52 ] and Grespan et al [ 53 ], respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Catalase is a widely spread antioxidant enzyme in animal tissues. It protects tissues from hyperactive hydroxyl radicals through decomposing hydrogen peroxide (28,29) . In our study, Cat level was decreased significantly in treated Group due to formation of free radicals in heart and decreases its ability to detoxify reactive oxygen species.…”
Section: Parametersmentioning
confidence: 99%